Molecular dynamics study of transport mechanisms in desalination membranes - Zhang, Hui (Nanyang Technological University, 2020)
Under the stress of water shortage and the need of reducing energy consumption, advancing the membrane technology continues to benefit the desalination applications. Research on transport mechanisms of desalination membranes drives the improvement of traditional membrane materials and development of novel membrane materials. It is challenging to use experimental approaches to probe solvent and solute transport at the nanoscale, thus making molecular dynamics (MD) simulations a necessary tool in the research of membrane transport. The thesis is dedicated to investigating the relationships between membrane structure and membrane transport, with the objectives of improving the fundamental understanding and the tailored design of next-generation membranes. The polyamide (PA) layer in thin-film-composite membranes and graphene (GE) membranes were studied as the representatives of traditional membrane materials and novel nanomaterials, respectively. Throughout the thesis, the limitations and validations of MD as well as the implications of MD results to the classic macroscopic theories were discussed to address the utility of MD simulations. In conclusion, membrane structures can be optimized in MD to enhance water transport and salt rejection. New molecular insights into the composition-structure-property relationships of desalination membranes were obtained, and the transport mechanisms were identified. Furthermore, molecular level interpretations of the classic macroscopic transport theories were highlighted.